Peran Keluarga sebagai Institusi Pendidikan Gender: Sebuah Kajian - Ali Anwar, Muhamad; Umar Fauzi, Muhammad (Kartika: Jurnal Studi Keislaman, 2023)
In gender education, parents have a very important role in educating anddirecting their children, because if gender bias occurs in a family, this will greatlyinfluence the children's mindset in the future. Gender injustice in the family oftenmanifests in various forms, including marginalization of women, subordination(secondary) of women, stereotypes (negative labeling) against women, violence(violence) against women and longer and longer workloads (double burden). Thisstudy uses library research, by analyzing scientific publications related to gendereducation and the role of the family in education. The results of this researchshow that Islam views the family as an institution of human life that can providethe possibility of harm and happiness for family members both in this world andthe afterlife. In an Islamic perspective, children are a mandate from Allah SWTthat must be held accountable. One form of responsibility is providing educationfor the children in the family.